Childhood schooling: narratives and conceptions on childhood in initial teacher training in Portugal | Éducation scolaire de l'enfance: récits et significations dans la formation initiale des enseignants au Portugal - Fátima Pereira (2011)
This paper presents partial results from a study carried out as part of the work for a PhD thesis in Education Sciences whose purpose was to find out about and understand conceptions on childhood that are expressed in or related to initial teacher training for the lst cycle of basic education (1° CEB) 1 in Portugal since April 1974 (democratic revolution date) to 2004. The results that we present and discussed here emerge from narratives identified in the analysed discourses and what they allow us to note about the teacher's work and its relations with childhood government. The results interpretation is located in a socioepistemological and theoretical context of late modernity and the crisis of modem institutions, that affects the occidental societies, in general.